THE URGENCY OF INTERNATIONAL INVESTMENT AGREEMENTS (IIA) AND INVESTOR-STATE DISPUTE SETTLEMENT (ISDS) FOR INDONESIA - Sefriani, S (Jurnal Dinamika Hukum, 2018)
In recent years, there has been an increasing number of claims through investor state dispute settle-ment (ISDS) proposed by foreign investors to the host states. This has prompted some states review their international investment agreements (IIA) and their ISDS clauses. Indonesia has terminated many of its Bilateral Investment Treaties (BIT) as well. The research questions are 1) How is the urg-ency of IIA and ISDS for Indonesia; and 2) What kind of IIA and ISDS format that Indonesia should make to balance the state’s and foreign investor’s interest. The analysis results conclude that the existence of IIA and ISDS remains urgent for Indonesia, but it takes changes in terms of format like the new models made by many other host states. They involve redefinition of multi-interpretative terms and the exhaustion of local remedies. In addition, the non-automatic and mutual agreement ISDS arbitration which excludes the MFN clause should also provide the state's flexibility to protect the people’s prosperity through non-discriminating regulations.Keywords: IIA; ISDS; foreign investment